2013
DOI: 10.1108/bjm-07-2013-0110
|View full text |Cite
|
Sign up to set email alerts
|

Inspiration at work: is it an oxymoron?

Abstract: Purpose – The purpose of this paper is to present results of an exploratory cross-cultural study aiming to examine the role and meaning of inspiration in organisational settings to advance the contemporary understanding of inspiration and its manifestations. Design/methodology/approach – The study utilises Gadamerian philosophical hermeneutics to cultivate an understanding of the rationalisations of inspiration at work and to explore its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Zapata-Phelan et al (2009) also argue that intrinsic motivation exerts strong effect persistence, which becomes a key predictor of an employee's performance on complex tasks. In particular, an individual who is intrinsically motivated tends to be driven by an inherent interest in, and contentment with, the work itself, and thus is naturally drawn toward carrying out their work (Joo et al, 2010;Avramenko, 2014). Job satisfaction is widely defined as a pleasurable or emotional state derived from the contemplation of the appraisal of job experiences (Wilkin, 2013).…”
Section: Subsequent Mediating Effects Of Intrinsic Motivation and Job Satisfactionmentioning
confidence: 99%
“…Zapata-Phelan et al (2009) also argue that intrinsic motivation exerts strong effect persistence, which becomes a key predictor of an employee's performance on complex tasks. In particular, an individual who is intrinsically motivated tends to be driven by an inherent interest in, and contentment with, the work itself, and thus is naturally drawn toward carrying out their work (Joo et al, 2010;Avramenko, 2014). Job satisfaction is widely defined as a pleasurable or emotional state derived from the contemplation of the appraisal of job experiences (Wilkin, 2013).…”
Section: Subsequent Mediating Effects Of Intrinsic Motivation and Job Satisfactionmentioning
confidence: 99%
“…There are however considerable differences between these two approaches to leadership which are summarised in Table 1. While transformational leadership is concerned with transforming followers into high performers, inspirational leadership aims to inspire followers to higher achievements (Adair, 2009;Avramenko, 2014). Transformation usually entails a complete makeover and a concomitant resistance to change.…”
Section: Transformational Leadership Vs Inspirational Leadershipmentioning
confidence: 99%
“…Despite the growing body of research on inspirational leaders, the knowledge about inspiration as a discrete phenomenon remains largely abstract (Avramenko, 2013;Frese et al, 2003). In most studies (Han et al, 2016), it was found that there is a positive relationship between transformational leadership and knowledge sharing.…”
Section: Leadership Inspiration As Part Of Transformational Leadershipmentioning
confidence: 99%